Interictal Epileptiform Discharge Dynamics in Peri-sylvian Polymicrogyria Using EEG-fMRI - Cohen, Noa; Ebrahimi, Yoram; Medvedovsky, Mordekhay; Gurevitch, Guy; Aizenstein, Orna; Hendler, Talma; Fahoum, Firas; Gazit, Tomer (Frontiers in Neurology, 2021)
Tracing the dynamics of interictal epileptiform discharges (IEDs) in patients with epilepsy may reveal the location of epileptic activity sources, crucial for successful treatment in cases of focal drug-resistant epilepsy. Polymicrogyria (PMG) is a common malformation of cortical development often associated with seizures, with epileptic sources difficult to localize due to the complex and widespread lesion structure. In this case series IED dynamics were evaluated with simultaneous EEG-fMRI recordings in four patients with unilateral peri-sylvian polymicrogyria (PSPMG) by tracking BOLD activations over time: before, during and following IED appearance on scalp EEG. In all cases, focal BOLD activations within the lesion itself preceded the activity associated with IED appearance as modelled with a standard HRF, which showed stronger and more widespread activations. We therefore suggest that early hemodynamic activity corresponding to IEDs point to their epileptic source. These develop within a small area in the PSPMG lesion with structural properties that prevent the appearance of epileptic events’ electric field on the scalp and later propagate to neighboring structures which have the capacity to produce large currents recognized as IEDs on EEG.